Characteristics of the high temperature mechanisms of creep and recovery in graphite: part 1 - College of Aeronautics, (Cranfield) (College of Aeronautics, 1963)
An apparatus has been developed for determining the high temperature creep and recovery characteristics of graphite by applying torsional stresses to thin-walled tubes. This method has the advantages of a simple stress system, constant stress for constant load, easy rapid removal of load and the independence of the strain measurement from thermal expansion. Torsional, stress-strain curves show a decreasing modulus with increasing temperature from 2000 - 2850°C. The rate of creep in this range is increased by increasing temperature and stress. Recovery rate is not so sensitive to increasing temperature. Using a method developed for metals, where recovery can be subtracted from forward creep, a secondary creep rate is deduced. This rate, when plotted according to the Arrhenius' equation, yields an activation energy for secondary creep of 154 kcals over the temperature range 2100 - 2700°C. These results are critically examined and the future extension of the work discussed.